Penile Plication as Salvage Strategy for Refractory Peyronie's Disease Deformities. Issue 2 (March 2017) - Cordon, Billy H.; Sundaram, Varun; Hofer, Matthias D.; Kavoussi, Nicholas L.; Scott, Jeremy M.; Morey, Allen F.
ABSTRACT : Introduction: : We identified clinical and/or surgical factors contributing to failure of penile plication for Peyronie's reconstruction and assessed outcomes of repeat plications. Methods: : We conducted a retrospective review of patients who underwent penile plication between 2007 and 2016. Plication was performed after inducing an artificial erection intraoperatively using corrective longitudinal 2‐zero Ethibond™ sutures placed systematically in a uniform manner without circumcision. Penile length, and angle and direction of curvature were recorded, along with number and location of plication sutures and clinical outcome. Results: : Of 340 patients undergoing penile plication during the study period 7 (2.1%) underwent repeat plication for insufficient straightening. Two additional patients underwent salvage plication after initial surgery performed elsewhere. Median time to revision was 6 months (range 3.4 to 27.4). The most common clinical features at reoperation were severe erectile dysfunction in 5 cases (71%), multiplanar curvature in 5 (71%) and severe curvature (60 degrees or greater) in 3 (43%). Most revisions involved a greater number of sutures during revision (mean 9) compared to initial plication (6), and in 4 cases (44%) sutures were placed on the proximal shaft. After revision all cases were noted to be functionally straight, with a mean postoperative curvature of 4 degrees (range 0 to 20) at a median followup of 27 months (3 to 76). Conclusions: : Inadequate correction of Peyronie's disease curvature by penile plication is rare but salvageable by a second plication procedure. Poor erectile response to intracavernous injection intraoperatively may mask the severity of the deformity, thus leading to inadequate numbers of corrective sutures.